2014
DOI: 10.3390/w6113478
|View full text |Cite
|
Sign up to set email alerts
|

Using a Statistical Model to Examine the Effect of COD: SO42− Ratio, HRT and LA Concentration on Sulfate Reduction in an Anaerobic Sequencing Batch Reactor

Abstract: Taguchi statistical design, an orthogonal array (OA) method, was used to study the impact of the COD/SO4 2− ratio, hydraulic retention time (HRT) and linoleic acid (LA) concentration on sulfate (SO4 2− ) reduction in an anaerobic sequencing batch reactor using glucose as the electron donor. Based on the OA, optimum condition for maximum SO4 LA addition (level 3). In general, the Taguchi OA provided a useful approach for predicting the percent SO4 2− reduction in inhibited mixed anaerobic cultures within the fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…A three factor three level Taguchi design was used for conducting the experimental run (Table 1) as described by Singh et al [25]. The factors investigated in this study include LA concentration, COD/SO4 …”
Section: Sulfate Reduction Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A three factor three level Taguchi design was used for conducting the experimental run (Table 1) as described by Singh et al [25]. The factors investigated in this study include LA concentration, COD/SO4 …”
Section: Sulfate Reduction Studiesmentioning
confidence: 99%
“…During the inhibition studies, the cultures were incubated with LA for 24 h prior to initiating the experiment (adding SO4 2− and glucose). , respectively; COD = Chemical oxygen demand; LA = linoleic acid; SO 4 2− = sulfate and ASBRs = anaerobic sequential batch reactors; The experiment design is based on the Taguchi model described by Singh et al [25]; Cultures fed 0 g·L…”
Section: Sulfate Reduction Studiesmentioning
confidence: 99%
“…Generally Chemical Oxygen Demand (COD)-to-sulphate (SO 4 2− ) ratio is a parameter widely used to control biological sulphate reduction and as well as the methane production. It has been shown that the competition of SRB was more pronounced at low COD/SO 4 2− ratio in the wastewater (Singh et al 2014). The consumption of organic substrates in sulphate-laden wastewater is strongly dependent on the COD/SO 4 2− ratio (Sarti and Zaiat 2011).…”
Section: Introductionmentioning
confidence: 99%